Reading Instructional Level from a Print-Processing Perspective. Issue 6 (2nd November 2019) - Morris, Darrell; Trathen, Woodrow; Gill, Tom; Perney, Jan; Schlagal, Robert; Ward, Devery; Frye, Elizabeth M.
Abstract: This study addressed the concept of reading instructional level. First, we reviewed the history of the concept, including some recent criticisms of its validity (Schwanenflugel & Knapp, 2017 ; Shanahan, 2014 ). Next, we examined, from an instructional-level perspective, the oral reading performance of 248 third graders. We divided the sample into quartiles (based on third-grade reading rate) and tested for between-quartile differences in the students' reading of second-, third-, and fourth-grade passages. A major finding was that the lowest quartile differed significantly from the other quartiles in oral reading accuracy and rate, showing, at best, a second-grade print-processing level at the end of third grade. Finally, we considered how our findings raise old—and still controversial—questions about the best way to provide instruction to low-achieving readers in the elementary grades.